Distribution of photoassimilates in sink organs of plants of Solanaceas, tomato and potato. A review - León-Burgos, Andres Felipe; Beltrán Cortes, Gina Yuret; Barragán Pérez, Andrea Liliana; Balaguera-López, Helber Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Tomato and potato crops are agricultural products of great importance worldwide due to their nutritional and industrial value. The distribution of photoassimilates in the sink organs of these crops depends to a great extent on the metabolism and partition of carbon generated in the photosynthetic processes, on the dynamics of both of the source and sink organs as the activity of enzymes linked to the metabolism of sugars and environmental and nutritional conditions. The objective of this paper was to review and discuss current knowledge of the distribution of photoassimilates in the sink organs and factors that can affect this mechanism in the tomato and potato crops. Based on information collected in recent research and review articles, it is reported that around 80% or 90% of the photoassimilates produced in the source organs in tomato and potato crops are transported or translocated to the sink organs of commercial interest (fruits and tubers). Both source/sink imbalance, as well as water stress and nutritional deficiencies, especially nitrogen and potassium significantly affect the distribution of photoassimilates. In contrast to the effects of the quality of light, it can improve the loading of photoassimilates in the sink organs and improve quality attributes of these such as increases in the size and concentration of sugars. However, more research is still needed to corroborate this effect, especially under field or greenhouse conditions in tropical regions.